Less known but greatly feared: Cervical cancer in Ethiopia community awareness - Nega Jibat; Rahma Ali; Wondimagegn Adissu; Gerezgiher Buruh; Alemseged Abdissa; Gelila K. Goba; Suzanne M. Garland; Nigisti Mulholland; Kim Mulholland; Demisew Amenu (Heliyon, 2024)
To improve a community's awareness and attitude towards cervical cancer, strong evidence is needed to inform contextually appropriate policies. This study aims to explore community awareness about cervical cancer from the perspective of women, men and health extension workers (HEWs). The research was conducted from May to July 2021 in Jimma, Ethiopia. A total of 23 in-depth interviews were conducted. The study included married and unmarried women (15–19 and 25–29 years old), men of similar ages (married and unmarried), and HEWs. Furthermore, eight separate focus group discussions (FGDs) were conducted with both men and women. Thematic analysis was used to draw findings from the interviews and FGDs. Community awareness about cervical cancer was very limited. However, people who knew of it believed that cancer is fatal. A few participants were aware of cervical cancer through its symptoms, but most people did not know it by name and had never heard about HPV as the cause of cervical cancer. There was little understanding of HPV risk, transmission factors, prevention, vaccination, screening, or treatment. Participants considered their participation in this study as their first chance to learn about the disease. HEWs had limited knowledge about HPV and cervical cancer. Study participants demonstrated favorable attitudes towards HPV vaccination, cervical screening, and treatment after they received basic information about cervical cancer from the data collectors. Participants and HEWs strongly suggested awareness creation programs for the wider community members, including active involvement of men and HEWs in cervical cancer interventions. There is a critical information gap regarding cervical cancer, its cause and risk factors, HPV transmission, cervical screening, and treatment programs. Limited community awareness leads to poor uptake of cervical screening in the few settings where it is available. Therefore, community awareness programs about HPV, cervical cancer, and available services should improve the community's awareness of cervical cancer and HPV.